(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2008)
Indomethacin (IM) sustained release microcapsules were successfully prepared using ethyl cellulose (EC) and hydroxy propyl methyl cellulose phthalate (HPMCP) by o/w emulsification-solvent evaporation technique. The prepared microcapsules were evaluated for size, shape, drug content and in vitro drug release. The microcapsules show sustained release curves at pH 7.2 phosphate buffer for up to 6 h. The data obtained from the dissolution profiles were compared in the light of different kinetics models and the regression coefficients were compared. The in vitro dissolution study confirmed the Higuchi-order release pattern. Particle size and release data analysis from five consecutive batches prepared in the laboratory indicated suitable reproducibility of the solvent evaporation process. The release rate increased exponentially with the addition of HPMCP in EC. IM release rate was observed highest with the highest concentration of HPMCP (3:7 ratio of EC:HPMCP), used in the present studies. On the other hand, IM release rate was lowest when EC and HPMCP combination was used at the ratio of 10:0. When percent of HPMCP was increased, the particle size of microcapsules was decreased. Key words: Indomethacin, sustained release, microcapsule, HPMCP, EC, Higuchi-order Â DOI = 10.3329/dujps.v7i1.1223 Dhaka Univ. J. Pharm. Sci. 7(1): 83-88, 2008 (June)